White matter lesions and DTI metrics related to various types of dysfunction in cerebral palsy: A meta-analysis and systematic review. - Yu Jiang; Gang Liu; Bowen Deng; Xiaoye Li; Jingpei Ren; Yi Zhao; Chuanyu Hu; Lin Xu; Feng Gao; Xiaohong Mu (PLoS ONE)
Background Assessing various types of dysfunction in cerebral palsy is a key factor in the treatment and rehabilitation of patients. The objective of this study was to use meta-analysis and systematic review to identify the specific white matter lesions and DTI metrics strongly associated with various types of dysfunction in cerebral palsy. Methods We conducted a literature search of PubMed, Embase, Cochrane Library and Web of Science databases to identify trials published that had evaluated the correlation between DTI metrics in sensorimotor pathways and function scores in cerebral palsy. Correlation coefficient (r) values were extracted for each study, and the extent of r was quantitatively explored. The remaining part of the study was analyzed qualitatively. Results 46 studies involving 1458 children with cerebral palsy, were included. 19 articles for Meta-analysis and 27 articles were descriptively analyzed. DTI metrics such as FA、MD in both sensory and motor pathways significantly correlated with various function ratings. In overall motor dysfunction, compared with the CST and PTR, FA of the PLIC correlated more strongly with GMFCS, and showed no significant heterogeneity (r = -1.28, confidence interval [CI]-1.70 to -0.87,I2 = 38.2%,P = 0.233). In upper limb dysfunction, compared with the AHA and MA2, FA of the CST correlated more strongly with BBT, and showed no significant heterogeneity (r = -0.56, confidence interval [CI]-0.78 to -0.34,I2 = 0.0%,P = 0.511). Lower limb dysfunction and other dysfunctions we used qualitative analysis. The qualitative analysis offered a concise overview of each investigation. Conclusions This study basically identifies the specific white matter lesions corresponding to overall motor dysfunction, upper limb and lower limb motor deficits and other dysfunctions in patients with cerebral palsy, as well as the associated DTI metrics.